After the famine Irish agriculture, 1850-1914 - Turner, Michael Edward (Cambridge University Press, 1996)
After the Famine examines the recovery in Irish agriculture in the wake of the disastrous potato famine of the 1840s, and presents an annual agricultural output series for Ireland from 1850 to 1914. Michael Turner's detailed 1996 study is in three parts: he analyses the changing structure of agriculture in terms of land use and peasant occupancy; he presents estimates of the annual value of Irish output between 1850 and 1914; and he assesses Irish agricultural performance in terms of several measures of productivity. These analyses are placed in the context of British and European agricultural development, and suggest that, contrary to prevailing orthodoxies, landlords rather than tenants were the main beneficiaries in the period leading up to the land reforms. After the Famine is an important contribution to an extremely controversial area of Irish social and economic history